Dar Voz aos Cuidadores: um jogo para o cuidador familiar de um doente dependente - Fernandes, Carla Sílvia; Angelo, Margareth; Martins, MM (Universidade de São Paulo, 2017)
Objective: To construct and assess a board game created to promote the effective transition of family members into caregivers of dependent individuals. Method: This was a qualitative exploratory and descriptive case study conducted with family caregivers of dependent individuals. Results: The study resulted in the conceptualization, construction, and assessment of the board game. The game proved to be an important family evaluation tool, enabling open communication and interventions in family dynamics. Conclusion: The results showed that the game can help build new family narratives, providing an opportunity for open communication, expression of problems and sharing, representing an important family evaluation and intervention strategy.
Giving Voice to Caregivers: a game for family caregivers of dependent individuals
Dar Voz aos Cuidadores: un juego para el cuidador familiar de un enfermo dependiente
Keywords: Caregivers; Family; Aged; Family Nursing.